PNEUMOTÓRAX CATAMENIAL: UM RELATO DE CASO - Larissa Amorim Silva; Isadora Coelho Matos; Rayane Carneiro de Amorim; Conjeto Luiz da Silva Neto; Fabiano Alves Squeff (UniEVANGÉLICA, 2018)
Objective: To report an unusual type of spontaneous pneumothorax in a patient with endometriosis. Case description: A 43-year-old female patient with endometriosis presented five episodes of spontaneous pneumothorax in which all had a relationship with the menstrual cycle, and in two, chest drainage was required. At the last hospitalization, the patient was dyspneic at admission, with decreased vesicular murmur in the right hemithorax. Chest X-ray showed pneumothorax and CT scan indicated no lesions or blisters, and video-assisted thoracoscopy was indicated. Lesions were found with diaphragm fenestration on the right. In this way, it was indicated the frenorrafia, pleurodese with talc and chest drainage. Patient presented good response, satisfactory pulmonary expansion, being discharged on the third day after surgery and referred to a gynecology outpatient clinic. Conclusions: from the clinical case, the importance of the investigation of catamenial pneumothorax and endometriosis in women of childbearing age with repetitive spontaneous pneumothorax to the menstrual cycle is noted.